Differential expression and evolution of three tandem, interleukin-1 receptor-like 1 genes in rainbow trout (Oncorhynchus mykiss). (October 2018) - Shaw, Cassidy H.; Gao, Guangtu; Wiens, Gregory D.
Abstract: Interleukin-1 receptor-like 1 (Il1rl1 or ST2), a member of the interleukin-1 receptor family, has pleiotropic roles including tissue homeostasis, inflammation, immune polarization, and disease resistance in mammals. A single orthologue was previously described in salmonid fish; however, a recently improved genome assembly of rainbow trout ( Oncorhynchus mykiss ) revealed three adjacent, tandem il1rl1 orthologues on chromosome Omy 03. Here, we report the genomic organization and evolution of the three il1rl1 genes ( il1rl1α, il1rl1β, il1rl1γ ), and use both RNA-seq and gene-specific qPCR methods to quantify expression patterns. Nucleotide sequence homology between the three genes is >95% and each predicted protein contains three IG/IG-like domains, a transmembrane region and a TIR domain. The amino acid sequence homology of the rainbow trout il1rl1 genes are highly related to two functional copies in Atlantic and Coho salmon (∼94%) but relatively low (22–26%) with avian and mammalian species. Transcript abundance measured by RNA-seq in 15 tissues of healthy adult rainbow trout indicate constitutive expression of each gene. In whole body lysates, il1rl1α was shown to have >20 fold mRNA expression compared to il1rl1β and il1rl1γ as measured by qPCR assays specific to il1rl1α or il1rl1γ, as well as a multi-gene qPCR assay ( il1rl1α, β, γ ). Unrooted phylogenetic trees grouped the rainbow trout il1rl1 genes apart from other interleukin-1 receptor family genes and genomic comparisons identify preserved synteny between mammals, birds and salmonids albeit a pseudogene is present in both Atlantic salmon and Coho salmon. Phylogenetic analyses suggest that the three genes arose by tandem duplication but are inconclusive whether these events occurred prior-to or after salmonid speciation. These findings further the understanding of interleukin receptor family evolution and their contribution to teleost immune function. Highlights: The rainbow trout genome contains three tandem, interleukin-1 receptor-like 1 ( il1rl1 ) genes exhibiting >95% aa homology. The three genes ( il1rl1α, il1rl1β, il1rl1γ ) were expressed in fifteen tissues of healthy rainbow trout. Il1rl1α expression in juvenile rainbow trout was 68- and 45-fold higher relative to il1rl1β and il1rl1γ, respectively. Phylogenetic analysis suggests expansion through tandem gene duplication.